Penerapan Sistem Informasi Pencarian Tata Letak Buku Pada Perpustakaan Fakultas Ilmu Sosial Dan Ilmu Politik Universitas Malikussaleh - Yessy Afrilliai; Suci Ramadani (Jurnal Sains dan Teknologi, 2021)
In the library of the Faculty of Social and Political Sciences, the search process for book layouts has not been well organized, where students and officers are still doing the seacrh process manually, namely officiers and students will come one by one books helves to find where the desired book is located. A process like this can complicate and slow down staff and students in the process of seacrhing for books, so that the author builds a web-based book layout search system that is more optimal and well-organized. To make it easier for students to find the location of the desired book and reduce the problems that occur in the book search process and help the staff work process more efficiently. This book layout search system is web-based, making it easier for students to find the desired book. The steps used in this research are requirements analysis, system design and system testing. The design of this system is designed using structured diagrams, namely Context Diagrams, data flow diagrams or called DFD, Entity Relationship Diagrams (ERD) and database design or called file design or called file design using MySQL. Meanwhile, for data collection using observation and literature study